A novel class of azatricyclononanes: pentasubstituted cyclopropanes from an uncatalysed reaction - Harris, L; Gilpin, M; Thompson, A; Cowley, A; Moloney, M (2009)
The direct and versatile stereoselective synthesis of a novel class of cyclopropyl derivatives of pyroglutamic acid is reported, using substituted diaryldiazo compounds. The course of the reaction has been investigated, and yields of substituted fluorenylcyclopropanes are greater than those of diphenylmethylcyclopropane analogues. © 2009 Elsevier Ltd. All rights reserved.